SISTEM PENUNJANG KEPUTUSAN PENERIMAAN KARYAWAN DENGAN MENGGUNAKAN METODE MADM SAW - Erik Kurniadi; Didi Damhudi (Universitas Kuningan, 2016)
Decision-making in determining the prospective employee is a crucial issue in a company to get the right staff and ideal staff. This decision is generally described as a case in which a companyâ€™s person HRD that must choose and sort out prospective employees of various criteria according to a decree issued by the head of the company. The decision-making system aims to provide recommendations for decision making in the selection to determine the employees objectively. To support the decision-making process used method of Multiple Attribute Decision Making (MADM) Simple Additive Weighting (SAW) process which determines the weight values for each attribute, and then proceed with the process of sorting and ranking will be automatically selected the best of a number of alternative.Applications used is WEB based applications using PHP programming language and MySQL database, while for the system design using the Data Flow Diagram. Development method using SDLC waterfall model. User of this application is HRD government offices that have been using this system and the application. In the process, the use of the application can perform data management prospective servants, the management of assessment criteria, the calculation of the test results can be displayed in a report.This application can help a variety of public and private agencies. PT Surya Â Inti Ciremai has used this application in managing the data in real-time. Of course, the use of these applications can be more efficient business processes that previously were done manually which business processes are recorded in the general ledger.